ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MODEL ALTMAN, SPRINGATE, OHLSON, ZMIJEWSKI, FOSTER DAN GROVER (Studi Kasus pada Perusahaan Pertambangan Tahun 2012-2016) - Muhsin N Bailusy; Rinaldi Tamrin (Jurnal Manajemen Sinergi, 2017)
This study aims to determine which model is most appropriate in predicting bankruptcy with the Altman model, springate, Ohlson, Zmijewski, Foster and Grover, as well as differences from the six predictive models. Research type in research is quantitative with descriptive method. Population in this research is mining company that listed in BEI year 2012-2016. Technique of taking data in this research use purposive sampling method. In this study the sample used as many as 20 companies from 43 mining companies listed on the Stock Exchange 2012-2016. Hypothesis testing using One Way Anova Differential Test and Accuracy Level Calculation. The results showed that there were differences in the results of the analysis among the six predicted bankruptcy models used in this study are Altman, Springate, Ohlson, Zmijewski, Foster and Grover models. The Altman model has an accuracy of 34%, the Springate model has an accuracy of 54%, the Ohlson model has an accuracy of 94%, the Zmijewski model has an accuracy of 83%, the Foster model has an accuracy of 78% and the Grover model is 89%. Of the six models it is known that the Ohlson model is the most appropriate model used to predict bankruptcy in mining companies with an accuracy of 94%.